Economic burden of pulmonary arterial hypertension in Switzerland - Yuki Tomonaga; Mona Lichtblau; Silvia Ulrich; Sabina A. Guler; Patrick Yerly; Benoît Lechartier; Jean-Marc Fellrath; Anne Bergeron; Louise Bondeelle; Silviu-Mihail Chirila; Andrea Favre-Bulle; Sandro Stoffel; et al. (PLoS ONE, 2026)
Objectives Pulmonary arterial hypertension (PAH) is a rare, progressive condition associated with high morbidity and healthcare resource utilization. This study aimed to estimate the annual direct and indirect costs of PAH in Switzerland, from a societal perspective. Materials and methods A cross-sectional cost-of-illness study was conducted across six Swiss PAH centres between April and December 2024. Adult patients with confirmed PAH (World Health Organization [WHO] Group 1) were invited to complete a standardized questionnaire on work productivity losses, informal care, and healthcare utilization outside the enrolling centre. Clinical data on hospitalizations, outpatient visits, diagnostics, and treatments at the enrolling centre were extracted from medical records. Disease-specific costs were calculated by multiplying resource use and work losses by Swiss-specific unit costs and extrapolated to one year. Estimates were stratified by WHO functional class (WHO-FC) and ESC/ERS 2022 risk strata. Results Among 124 participants aged between 18 and 89 years, the mean disease-specific total annual cost per patient was €138,958. Direct healthcare costs represented 78.5% of this amount (€109,114), driven primarily by pharmacological treatment (65% of total costs). Indirect costs amounted to 21.5% (€29,844). Costs increased with disease severity, ranging from €81,957 in WHO-FC 1 to €166,569 in WHO-FC 4, and from €130,970 in ESC/ERS low risk to €291,728 in ESC/ERS high risk. The total national burden was estimated at €48.5 million annually. Conclusions PAH imposes a substantial economic burden in Switzerland, largely due to treatment costs and productivity losses. These findings highlight the need for strategies to reduce disease progression and associated societal costs.